Strengthening Environmental Literacy Through Digital Reading Corners in the Kedunglurah Village Community - Mohamad Aris Murtadho; Ivon Nurhabibah; Ahdini Ahdini; Lutfiatus Zahro; Neris Eka Fitriani; Fatkhul Janah; Muhamad Yusuf Wahfihudin (LP2M Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2024)
Purpose: This study analyzes the effectiveness of the Digital Reading Corner (POCADI) in increasing reading interest in Kedunglurah Village, Pogalan District, Trenggalek Regency. The problem addressed is the low interest in reading among rural communities caused by limited access to quality reading materials and the absence of technology-based literacy facilities. Method: The method used in this research is Participatory Action Research. PAR (Participatory Action Research) is a collaborative research approach that emphasizes the direct and active involvement of participants throughout the research process. This method aims to empower communities by involving them in the process of identifying problems, formulating solutions, and implementing actions to address them. Practical Applications: POCADI effectively enhances reading interest by providing practical access to digital materials, familiarizing youth with technology, and fostering a sustainable literacy culture. It also integrates environmental education, encouraging awareness of cleanliness and waste management. Additional benefits include cost efficiency, improved human resources, and potential replication in other villages. Conclusion: Despite challenges such as limited devices, low digital literacy, and weak promotion, POCADI has proven effective in transforming rural literacy and strengthening community awareness of environmental sustainability.